Delithiated B-Spodumene of lithium mineral extracting process, a potential supplementary cementitious material for geopolymer & conventional concrete applications with reduced CO2 footprint - Didar S. Cheema (Revista ALCONPAT)
This paper presents the feasibility of De-lithiated B-Spodumene (DBS) use, in combination with conventional SCMs - slag (GGBFS) like low calcium fly ash by-product, for non- structural sustainable geopolymer concrete applications such as: backfill, bedding material and non-structural concrete applications (foot path, rest areas, traffic islands’ infill, etc) with reduced CO2 footprint. Rechargeable batteries that store energy in the form of chemicals and convert it into electrical energy on demand are seen as the green alternative. The key ingredient in these batteries is lithium. Lithium is processed from natural a-Spodumene to B-Spodumene. The DBS in its leached form as lithium slag, comprises of quartz (SiO2) and aluminum oxide (Al2O3), like fly ash. They can be potential alternative SCMs for geopolymer/ conventional concrete applications DBS, either fully or partially, in combination with other common Supplementary Cementitious Materials (SCMs).